2005
DOI: 10.1167/iovs.05-0426
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Control of Gene Expression in the Mouse Meibomian Gland

Abstract: These findings demonstrate that testosterone regulates the expression of numerous genes in the mouse meibomian gland and that many of these genes are involved in lipid metabolic pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 53 publications
1
73
1
1
Order By: Relevance
“…Steroid sulfatase, 3beta-hydroxysteroid dehydrogenase, 17beta-HSD types 1 and 3, aromatase, glucuronosyltransferase, in the human lacrimal gland, Meibomian gland, cornea, and conjunctiva, and the steroid sulfotransferase only in the lacrimal and Meibomian glands [8]. A number of genes are regulated by testosterone and E2 and/or progesterone in the lacrimal and Meibomian glands, and many of these genes are related to lipid metabolism, tyrosine kinases, immune factors, extracellular matrix components, steroidogenesis, and many others [6,8]. The underlying receptor signaling pathways are not obvious, but likely include genomic and non-genomic mechanisms.…”
Section: Extra-neural Oestrogen In the Retinamentioning
confidence: 97%
See 3 more Smart Citations
“…Steroid sulfatase, 3beta-hydroxysteroid dehydrogenase, 17beta-HSD types 1 and 3, aromatase, glucuronosyltransferase, in the human lacrimal gland, Meibomian gland, cornea, and conjunctiva, and the steroid sulfotransferase only in the lacrimal and Meibomian glands [8]. A number of genes are regulated by testosterone and E2 and/or progesterone in the lacrimal and Meibomian glands, and many of these genes are related to lipid metabolism, tyrosine kinases, immune factors, extracellular matrix components, steroidogenesis, and many others [6,8]. The underlying receptor signaling pathways are not obvious, but likely include genomic and non-genomic mechanisms.…”
Section: Extra-neural Oestrogen In the Retinamentioning
confidence: 97%
“…Historically, this system, including lachrymal and Meibomian glands, cornea, conjunctiva and the lids has been suggested to be target of steroids and to be especially linked to the gender and hormonal fluctuations. Successively, it was found that these structures possess oestrogen, androgen, progesterone, mineralcorticoid and glucocorticoid receptors [6][7][8][9][10][11][12], and steroidogenic enzymes, listed below, suggesting an intrinsic ability of metabolizing circulating steroids. Steroid sulfatase, 3beta-hydroxysteroid dehydrogenase, 17beta-HSD types 1 and 3, aromatase, glucuronosyltransferase, in the human lacrimal gland, Meibomian gland, cornea, and conjunctiva, and the steroid sulfotransferase only in the lacrimal and Meibomian glands [8].…”
Section: Extra-neural Oestrogen In the Retinamentioning
confidence: 99%
See 2 more Smart Citations
“…Mammalian Meibomian glands that line the eyelids and produce lipids can be used for biosynthetic studies (Anderson and Kolattukudy 1985;Kolattukudy et al 1985a;Schirra et al 2005). In recent years sebocytes-derived immortalized cell lines that are capable of differentiation into sebum producing cells have been developed.…”
Section: Tissues Suitable For Biosynthetic Studiesmentioning
confidence: 99%